2019
DOI: 10.1016/j.ijid.2019.03.004
|View full text |Cite
|
Sign up to set email alerts
|

MRI evaluation of pulmonary lesions and lung tissue changes induced by tuberculosis

Abstract: Objective: To evaluate the utility of magnetic resonance imaging (MRI) with an advanced motion correction technique in characterizing lung tissue changes and lesions induced by pulmonary tuberculosis (TB). Methods: Sixty-three subjects with computed tomography (CT) features of pulmonary TB underwent lung MRI. All subjects with pulmonary TB were confirmed by acid-fast bacillus (AFB) testing or the detection of Mycobacterium tuberculosis. T2-weighted turbo spin echo (TSE) sequence MRI with the MultiVane motion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…They have been used as phantoms for lung ultrasound surface wave elastography [55] and for lung MR imaging [56]. Different MRI pulse sequences, including FSE (fast spin echo) and PROPELLER (periodically rotated overlapping parallel lines with enhanced reconstruction), have been tested, during the last decade, for detection and identification of different pulmonary changes induced by tuberculosis [9][10][11]. These methods are not particularly effective for imaging of lung tissue, characterized by fast signal decay due to very short T 2 /T 2 * relaxation times.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have been used as phantoms for lung ultrasound surface wave elastography [55] and for lung MR imaging [56]. Different MRI pulse sequences, including FSE (fast spin echo) and PROPELLER (periodically rotated overlapping parallel lines with enhanced reconstruction), have been tested, during the last decade, for detection and identification of different pulmonary changes induced by tuberculosis [9][10][11]. These methods are not particularly effective for imaging of lung tissue, characterized by fast signal decay due to very short T 2 /T 2 * relaxation times.…”
Section: Discussionmentioning
confidence: 99%
“…When diagnosing pulmonary diseases, the MRI can be used to detect disease-induced changes in the lungs [9][10][11]. MRI is especially attractive when dealing with pediatric patients [12] and pregnant women [13].…”
Section: Introductionmentioning
confidence: 99%
“…For the examination of pulmonary tuberculosis, Zeng et al [ 46 ] compared the utility of MRI and CT using a T2-W fast spin-echo sequence with rotating phase-encoding for motion compensation. In a series of 63 patients, the authors clearly identified diagnostically relevant pathology such as tree-in-bud sign, ground-glass opacity, consolidation, masses and cavitations [ 46 ]. The sensitivity for non-calcified nodular lesions was consistent with previous reports (50.0%, 91.1% and 100% for nodules sizes <5 mm, 5–10 mm and >10 mm, respectively).…”
Section: Common Indicationsmentioning
confidence: 99%
“…Assuming an adequate examination technique, MRI diagnostics is on a par with CT for these diseases. This includes all lung diseases with alveolar exudation and infiltration by infections [24,25], tissue proliferation such as tumors or metastases [22], malformations such as sequesters [26] and of course cystic fibrosis, which is particularly important in pediatric pulmonology [27].…”
Section: General Recommendations For Good Lung Magnetic Resonance Imamentioning
confidence: 99%
“…c Apparent diffusion coefficient (ADC) map from the axial diffusion-weighted imaging sequence: The low ADC values (arrow) prove the purulent content within the cave shows high MRI signal (Figs. 3 and 4) [24,25]. MRI is not commonly used in the examination of simple pulmonary inflammation, but it can be useful if complications, for example abscess formation, are suspected (Figs.…”
Section: Inflammatory Changesmentioning
confidence: 99%